Posting-related attributes driving differential engagement behaviors in online travel communities. Issue 5 (August 2018) - Fang, Jiaming; Li, Juan; Prybutok, Victor R.
Highlights: This study explores what and how posting-related attributes drive engagement behaviors. Three positively valenced engagement behaviors in online communities are investigated. Attributes from the information-, source-, and receiver-level affect engagement. Attributes exhibit differential effectiveness in triggering users to engage. Source-level attributes exert the largest impact across the three engagement behaviors. Abstract: Users' engagement behaviors such as likings, sharing and social interactions in online communities are critically important to the viability and the ultimate success of these communities. However, empirical research investigating which posting-related attributes driving these participation behaviors still lags. The purpose of this study is to understand what and how posting-related attributes drive the engagement behaviors. Using travelogue data from a large traveling knowledge-sharing community, we used econometric models to investigate and compare the antecedents leading to three different kinds of engagement behavior that users exhibit in online communities (i.e., consuming, contributing, and creating). The results reveal that five attributes are associated with these engagement behaviors. These attributes demonstrate the differential effectiveness on the engagement behaviors with different intensities. Our empirical findings provide both theoretical and practical implications for online community operators to build a vibrant and successful online community.